1996
DOI: 10.5558/tfc72393-4
|View full text |Cite
|
Sign up to set email alerts
|

One and two years impact of commercial thinning on spruce budworm feeding ecology and host tree foliage production and chemistry

Abstract: Field rearing experiments of spruce budworm, Choristoneura fumiferana (Clem.), were conducted in conjunction with foliar chemical analyses, one and two years after a commercial thinning (removal of 25% stand basal area) in a 50-year-old balsam fir, Abies balsamea (L.) Mill., stand. The first year after thinning, spruce budworm larvae reared on the residual trees developed five days faster and removed 43% more foliage than those reared on control trees, but in the second year they developed two days faster and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 18 publications
4
43
1
4
Order By: Relevance
“…The principal monoterpenes that are produced by host tree foliage and their concentrations have been determined in several previous studies (Bauce et al 1994, Bauce 1996, Carisey & Bauce 1997a, 1997b, 1997c, Kumbasli et al 2011. Based on these data, six monoterpenes (α-pinene, bornyl acetate, camphene, δ-3-carene, terpinolene, tricyclene -Sigma-Aldrich, Milwaukee, WI, USA) were tested at different concentrations (Tab.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The principal monoterpenes that are produced by host tree foliage and their concentrations have been determined in several previous studies (Bauce et al 1994, Bauce 1996, Carisey & Bauce 1997a, 1997b, 1997c, Kumbasli et al 2011. Based on these data, six monoterpenes (α-pinene, bornyl acetate, camphene, δ-3-carene, terpinolene, tricyclene -Sigma-Aldrich, Milwaukee, WI, USA) were tested at different concentrations (Tab.…”
Section: Methodsmentioning
confidence: 99%
“…Concentrations of these compounds, like others present in the host plant foliage, are subject to spatial and temporal change. It is well known that terpenoid concentrations in foliar tissues generally increase with light intensity (Spring et al 1986, Bryant et al 1987, Gref & Tenow 1987, with nutrient availability (Björkman et al 1998), and following stand thinning, for example, in balsam fir (Bauce 1996, Lamontagne et al 2000, Fuentealba & Bauce 2012. Bauce et al (1994) showed that monoterpenes are positively correlated with the strong resistance offered by young balsam fir trees against budworm attack, compared to mature individuals.…”
Section: Introductionmentioning
confidence: 99%
“…This low growth for both thinned and control stands before thinning may have been due to the spruce budworm outbreak, which occurred in the region in the late 1970s . Several studies have examined the interaction between spruce budworm outbreaks and CT (Bergeron et al, 1995;Bauce, 1996;Pothier, 1998) or pre-CT (Thibault et al, 1995;Tremblay, 2006). However, none of them deal with thinning conducted on a stand defoliated by spruce budworm a few years earlier.…”
Section: Growth Responsementioning
confidence: 99%
“…En outre, les EC permettent de maintenir la vigueur des tiges résiduelles et la hausse potentielle de sa résistance à la tordeuse des bourgeons de Fépinette {Charistormaraftmîferama (Clem.)) (Bauce 1996;Bédard et al 2003;Tremblay 2006). …”
Section: Mise En Garde/adviceunclassified